A novel ELISA using a recombinant outer membrane protein, rTp0663, as the antigen for serological diagnosis of syphilis. (February 2016) - Xu, Man; Xie, Yafeng; Jiang, Chuanhao; Xiao, Yongjian; Kuang, Xingxing; Zhao, Feijun; Zeng, Tiebing; Liu, Shuangquan; Liang, Mingxing; Li, Li; Wang, Chuan; Wu, Yimou
Highlights: A soluble recombinant version of a new Treponema pallidum outer membrane protein, known as Tp0663, has been produced for the diagnosis of syphilis. The recombinant protein exhibited a superior serodiagnostic performance to the ARCHITECT Syphilis TP chemiluminescent immunoassay (Abbott GmbH & Co. KG) when 3326 characterized serum samples were screened with the two tests. The Tp0663-based ELISA was in perfect agreement with clinical diagnosis (gold standard) with a κ value of 0.99, comparable to that of ARCHITECT Syphilis TP (0.96). Tp0663 may represent a novel candidate with highly accurate diagnosis for the seroscreening of syphilis. Summary: Background: The lack of Treponema pallidum -specific antigens with highly accurate diagnosis makes the diagnosis of syphilis challenging. Methods: A soluble recombinant version of a new diagnostic protein Tp0663 has been produced. The serodiagnostic potential of this protein was assessed by screening 3326 serum samples simultaneously evaluated by rapid plasma reagin and T. pallidum particle agglutination tests. Kappa (κ) coefficients were used to compare the concordance between clinical diagnosis and the Tp0663-based ELISA or the ARCHITECT Syphilis TP chemiluminescent immunoassay (Abbott GmbH and Co. KG). Results: Using the results of clinical diagnosis as the gold standard, the sensitivity and specificity of Tp0663 were found to be 98.83% (95% confidence interval (CI) 96.61–99.60%) and 100% (95% CI 99.88–100%), respectively. In comparison, the ARCHITECT Syphilis TP assay was found to have a lower sensitivity (97.27%, 95% CI 94.46–98.67%) and specificity (99.61%, 95% CI 99.32–99.78%). In particular, the ARCHITECT Syphilis TP exhibited a false-positive rate of 0.39%. Moreover, the ELISA was in perfect agreement with the gold standard, with a κ value of 0.99, comparable to that of ARCHITECT Syphilis TP (0.96). Conclusion: These results identified Tp0663 as a novel serodiagnostic candidate with great potential for developing novel tests for the diagnosis of syphilis.